Geographical analysis of the temporal and spatial relationships of land cover changes in the Rusafa district using geographical techniques - Mohammed, Shatha Abbas Jassim; Al-Azzawi, Thaer Mazher Fahmy (Al-Adab Journal, 2022)
The research aims to reveal the proportions of land cover changes and land uses in Al-Rusafa district for the period (1985-2020) through the integration between remote sensing techniques and geographic information systems and by using geographical analysis of natural and human factors and their temporal and spatial relationship and the resulting positive and negative changes that reflected their impact on the nature of And the trend of those changes, especially with regard to climatic elements and population increase, which led to urban sprawl on agricultural lands and other uses, and disruption of the environmental and planning balance of the study area in the absence of legal deterrence in it. The process of predicting the future of these changes was carried out on the basis of the Markov chain (CA-MARCOV). And for the year 2030, and in light of the nature and direction of the past and present changes, which resulted in negative changes in the percentage of water cover and agricultural use in favor of open and residential areas, and an increase in the rates of their future positive changes.